Evaluation of recombinant inbred lines based on morphological and biochemical parameters in Indian mustard (Brassica juncea L.) derived from Rohini × PBR-97 (Journal of Oilseed Brassica, 2026)
Among the rapeseed-mustard (Brassica spp.) group of crops Indian mustard (Brassica juncea L.) is the principal crop which accounts for approximately 85% of the total acreage under rapeseed-mustard. Here in this study, a set of 225 recombinant inbred lines (RILs) developed through a cross between high yielding commercially released Indian mustard cultivars Rohini and PBR-97. were evaluated in F6:7 generation during the Rabi season of 2012 -2013 and data were recorded for various morphological and biochemical parameters such as plant height, main shoot length, fruiting zone length, siliqua length, seeds/siliqua, biological yield/plant, 1000-seed weight, harvest index, seed yield/plant, oil content, and glucosinolates, fiber and phenol content. Significant genetic variation was observed among RILs for all the traits based on analysis of variance along with high genetic advance and high heritability for seed yield/plant, biological yield, 1000-seed weight, fibre and glucosinolates content. Seed yield/plant was found to be significantly and positively correlated with plant height, biological yield, number of seeds/siliqua and 1000-seed weight. Among these RILs, 25 RILs were identified as highly promising RILs on the basis of seed yield/plant which can be further used for multilocation testing for varietal release or used as parents in mustard breeding programs.